El aprovechamiento forestal en las concesiones forestales de la región Loreto y su aporte al desarrollo sostenible en la provincia de Maynas, región Loreto - 2021 - Panduro Cardenas, Robert Renzo (2023)
This study was carried out in Loreto region, in order to identify the contribution of forest concessions to sustainable development in Maynas province, Loreto region, 2021. From the obtained results, the extraction of raw material through the modality of forest concessions from 1986 to date, it was developed under the framework of three forestry laws such as Nº 21147, 27308 and 29763; of which Forestry and Wildlife Law 27308, reached the highest levels of production, in 2015 with 903,900 m3 of production. The Forestry and Wildlife Law 29763 has had a terrible behavior and therefore poor results and has put at risk the forestry activity of the region that extracts very low volumes of raw material. Loreto region is the one with the largest area granted in concession with 3,337,804.54 ha with 318 contracts, followed by Ucayali, which only has 151 concessions, but with an extension of 2,681,924.76, and Madre de Dios with 1,350,889.31 ha. With 1247 concessions. Loreto region has 70 primary transformation plants in operation by 2021, Maynas is the province with the largest number of operating plants with 36 units followed by Lacia de Mariscal Castilla with 12 operating units. The species that are most extracted and commercialized are bolaina, tornillo, catahua, capinuri capirona. The forest concessions in Loreto region do not contribute to the indicators of sustained development such as social, economic, rescuing the ecological indicator, but at high cost.